A new heterozygous mutation in the stop codon of CRYAB (p.X176Y) is liable for congenital posterior pole cataract in a Chinese family. (4th March 2021) - Yu, Yinhui; Xu, Jingjie; Qiao, Yue; Li, Jinyu; Yao, Ke
ABSTRACT: Background : The present study aims to identify the underlying genetic defects in a Chinese family with autosomal dominant congenital cataracts (ADCC). Methods : Detailed family histories and clinical data were recorded. Targeted exome sequencing of 54 known cataract-associated genes combined with high-throughput next-generation sequencing was conducted followed by Sanger sequencing and bioinformatic analysis to identify the causative gene lesion for the family. Results : A four-generation Chinese family with posterior pole type cataract were enrolled. Enrichment of targeted genes revealed a new heterozygous p.X176Y mutation in the stop codon of αB-crystallin ( CRYAB ) gene, which resulted in the loss of the stop codon and prolongation of the mutant protein by 19 amino acid residues (p.X176Yfs19*). Sanger sequencing showed complete co-segregation with the disease. The elongated mutant protein was predicted to be pathogenic by forming new α-helix and random-coil in the secondary structure as well as producing an extended strand in the tertiary structure, potentially leading to increased hydrophobicity and reduced protein stability. Conclusions : Our report added a new mutation in the spectrum of congenital cataracts. The data suggested that X176 residue in the COOH-terminal is of crucial importance for the αB-crystallin protein function which was valuable for further study of the pathogenesis of congenital cataracts. Abbreviations: CRYAB : αB-crystallin; DNA: deoxyribonucleic acid; PCR: polymerase chain reaction; TES: targeted exome sequencing; ACD: αB-crystallin domain.